In vitro anthelmintic activity of three medicinal plants. - *, Adeola; Adewole, I.B,; L.K, Olofintoye, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
In vitro anthelmintic assay of three medicinal plants was conducted to investigate which plants were anthelmintic. In vitro anthelmintic activity of all the three medicinal plants were carried out using earthworm at 50, 100, 200mg/ml of plant extracts from Vernonia amygdalina, Ocimum grattisimum and Talinum triangulare. Results showed that 200mg/ml was effective concentration for all the medicinal plants. Vernonia amygdalina showed faster anthelmintic than Ocimum grattisimum and Talinum triangulare.The plants can be used /employed in pharmaceutical industry to be used as anthelmintic drugs for treating livestocks affected with helminths.